2017
DOI: 10.1002/ente.201600512
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Electrolyzers for Production and Separation of Hydrogen from Sea Water using Naturally Abundant Solar Energy

Abstract: We report the design and development of a microfluidic electrolyzer for the continuous production and in situ separation of hydrogen fuel. A series of photovoltaic cells was integrated with a microchannel to produce a high‐intensity electric field under direct solar illumination, which electrolyzed the sea water in the microchannel. The rate of hydrogen production could be varied by tuning the electric field intensity or the flow rate of the sea water. The addition of an outlet near the cathode led to the in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 85 publications
0
10
0
Order By: Relevance
“…While the ion-selective membranes in PEM electrolyzers greatly limit the type of electrolyte that can be used in a given device, membraneless electrolyzers have been demonstrated in acidic, alkaline, and neutral solutions. 13,15,17 Water electrolysis is almost always performed in strongly acidic or alkaline environments, but operation in pH-neutral electrolytes is also of interest because (1) there should be fewer safety concerns compared with strongly caustic or acidic liquid electrolytes, and (2) a pH-neutral environment may enable the use of lower-cost catalyst and/or construction materials that normally corrode in acid or base. The electrolyte-agnostic nature of membraneless electrolyzers also makes them attractive for other electrolysis processes such as CO 2 electrolysis, 18 acid/ base production from brine, 19 and more.…”
Section: And the Curves Inmentioning
confidence: 99%
“…While the ion-selective membranes in PEM electrolyzers greatly limit the type of electrolyte that can be used in a given device, membraneless electrolyzers have been demonstrated in acidic, alkaline, and neutral solutions. 13,15,17 Water electrolysis is almost always performed in strongly acidic or alkaline environments, but operation in pH-neutral electrolytes is also of interest because (1) there should be fewer safety concerns compared with strongly caustic or acidic liquid electrolytes, and (2) a pH-neutral environment may enable the use of lower-cost catalyst and/or construction materials that normally corrode in acid or base. The electrolyte-agnostic nature of membraneless electrolyzers also makes them attractive for other electrolysis processes such as CO 2 electrolysis, 18 acid/ base production from brine, 19 and more.…”
Section: And the Curves Inmentioning
confidence: 99%
“…In another report Rarotra et al have used Y-shaped microfluidic electrolyzer in which the electrodes were positioned on the Y-arms (Fig. 13) [74]. They have run the electrolyzer with DC power, PV power using seawater, and found that the combination of PV cells with seawater produced the lowest volume of hydrogen because of the fluctuations in the solar illumination during the daytime.…”
Section: Recent Advancement Of Membrane-less Electrolyzers For Seawat...mentioning
confidence: 99%
“…The prototypes (Figure b) employed thin dividers downstream to aid product separation, and 2.8% product crossover was measured using in situ electrochemical sensors, in situ imaging, and gas chromatography . Rarota et al developed a microfluidic seawater electrolyzer with low power requirements coupled with a series of photovoltaic cells with a Y-shaped junction to facilitate H 2 separation at the outlet . They also developed a solar panel-integrated paper-based device employing graphite from a pencil deposition with reduced graphene oxide coating and seawater electrolyte .…”
Section: Devices and Applicationsmentioning
confidence: 99%
“…267 Rarota et al developed a microfluidic seawater electrolyzer with low power requirements coupled with a series of photovoltaic cells with a Yshaped junction to facilitate H 2 separation at the outlet. 268 They also developed a solar panel-integrated paper-based device employing graphite from a pencil deposition with reduced graphene oxide coating and seawater electrolyte. 269 Pang et al applied empirical correlations and electrochemical engineering design principles to present a framework using a parallel plate membraneless electrolyzer model system for evaluating the performance limits and guiding their design optimization.…”
Section: Electrolytic Cellsmentioning
confidence: 99%